Review of Business Actor’s Financial Behavior in the Ultra Micro Segment - Rosalina Puspitasari; Ellya Zulaikha (Institut Teknologi Sepuluh Nopember, 2023)
Micro, Small, and Medium Enterprises (MSMEs) have an essential role in the Indonesian economy due to their high economic resilience and contribute to gross domestic product and increased employment. The number of MSMEs reached 65.47 million units in 2019, or 99.99% of the total business in Indonesia, including the Ultra Micro (UMi) segment. The banking sector targets around 57 million UMi segment customers, but 30 million of them do not have access to formal funding sources because they are underprivileged and unbanked communities. Banking provides various services for business actors in the UMi segment regarding financing, deposits, and transactions. However, they have not been widely accessed and utilized due to a lack of understanding of these services. This study aims to recommend marketing strategies based on financial behavior and the needs of the UMi segment in banking services. The approach taken is Design Thinking. Data was collected through in-depth interviews with 8 (eight) respondents of the UMi Segment business actors aged 21–55 years, with a maximum turnover of IDR10 million a month. The findings of the study reveal the crucial role of friends and neighbors; the lack of clarity in recording transaction data; the vulnerability in financial management; the shame of saving